INFORMATION COMMUNICATION AND TECHNOLOGY UNDERGRADUATES’ PERCEPTIONS ON E-PORTFOLIO AS A TOOL IN A TECHNICAL COMMUNICATION COURSE - Khoo Mei Sui, Linda; Chai Sing, Hoo; Subatira, B; Kar Mee, Cheong (Journal of Human Capital Development (JHCD), 2019)
The demands for soft skills have arisen tremendously over recent years as universities incorporate these skills into their curriculum. Graduates need the technical knowledge as well as the soft skills in order to perform effectively in the workplace. This paper investigates the impact of an e-Portfolio in a technical communication course to enhance the information technology students’ soft skills in communication, critical thinking and problem solving and teamwork. The objective of the research is to find out the undergraduates’ perceptions on e-Portfolio as a tool in a technical communication course. An open-ended questionnaire was distributed to 65 students to elicit information at the end of the semester. The findings showed that most of the students’ found that e-Portfolio had helped them to improve their learning. This indicates that e-Portfolio has the potential as a tool to enhance students’ soft skills in their learning.